Beyond the Screen: An Interpretative Phenomenological Analysis of Undergraduate Students' Speaking Anxiety Under Strict Technological Deprivation - Abdurrohman Septiadi; Riskayadi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Most research on foreign language speaking anxiety has examined it through classroom anxiety scales, public-speaking contexts, or, more recently, online and AI-mediated learning; comparatively little is known about what happens when digital tools are deliberately withdrawn. This study explores how ten undergraduate students in Bangka Belitung Province experienced speaking anxiety during structured English-speaking activities conducted under strict technological deprivation, defined as the intentional, sustained removal of smartphones, chatbot applications, and internet access during a speaking task. Using Interpretative Phenomenological Analysis (IPA), semi-structured interviews were analyzed idiographically before cross-case synthesis, following Smith and Osborn's procedure. Rather than converging on a single tidy narrative, participants' accounts diverged in intensity, trajectory, and meaning. Five superordinate themes emerged: (1) digital concealment and the fear of being "found out," (2) the body's memory of the phone and the disruption of habitual cognitive routines, (3) uneven reckonings with technological dependency, ranging from reluctant insight to unresolved resentment, (4) biographical echoes, in which participants' anxiety was shaped by earlier, unrelated experiences of evaluation, and (5) divergent trajectories, including a negative case in which repeated exposure did not produce adaptation. The study argues that this form of anxiety is not fully explained by existing communication-apprehension or fear-of-evaluation constructs, and instead proposes viewing digitally mediated learners' phones and applications as an extension of a provisional communicative self, whose withdrawal exposes not only linguistic gaps but also identity-level vulnerabilities shaped by each learner's history. Implications for speaking pedagogy in technology-saturated, regional EFL contexts are discussed alongside the study's methodological limitations. Keywords: speaking anxiety; technological deprivation; Interpretative Phenomenological Analysis; digital dependency; identity; EFL learning